Analisis Efektivitas Jembatan Penyeberangan Orang (JPO) di Pasar Singosari - Tarsisius Sandro Jasar; Andy Kristafi Arifianto; Pamela Dinar Rahma (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2025)
Pedestrian overpasses (JPO) are facilities provided for pedestrians to minimize the risk of accidents when crossing the street, especially in areas with high traffic volumes. In the Singosari Market area, Malang Regency, there is fairly heavy vehicle and pedestrian traffic, but the usage of existing pedestrian overpasses (JPO) remains relatively low. This study aims to identify the physical condition of the JPO, evaluate the level of effectiveness of JPO users, and undertake efforts to improve the effectiveness of JPO usage in Singosari Market. The research method used is descriptive quantitative, with primary data collection through field observations, measurements of the JPO’s geometric dimensions, a pedestrian volume survey, and the distribution of questionnaires to JPO users. Additionally, secondary data was obtained from relevant agencies. The effectiveness of the JPO was measured by comparing the number of pedestrians using the JPO to the total number of pedestrians crossing the road. The results of the study indicate that the physical condition of the JPO at Singosari Market does not yet fully meet the standards set by the Ministry of Public Works and Public Housing in 2018. Furthermore, the level of effectiveness in JPO usage falls into the “moderately effective” category. Therefore, it is necessary to improve the quality of facilities, add supporting infrastructure, and conduct public awareness campaigns to ensure the optimal safety and effectiveness of pedestrian overpasses.